An all-dielectric 3D Luneburg lens constructed by common-vertex coaxial circular cones. (16th October 2019) - Chen, Jin; Lin, Yiyue; Peng, Gantao; Huang, Yixing; Zhang, Anxue; Song, Wei-Li; Chen, Mingji; Liu, Zhanwei; Fang, Daining
Abstract: An all-dielectric broadband 3D Luneburg lens has been designed and manufactured in our study, which is constructed by common-vertex coaxial circular cones. A prototype of the lens is fabricated using 3D printing technology. The far field of the, present lens is highly directive, incident waves are focused with highly concentration, and its operating frequency spans from 5 GHz to 20 GHz. It is also found that two highly directional beams are generated while two independent converged sources feed simultaneously at the edge of the lens. The intersection angle with the center of the lens is 90°, which indicates that the lens is an efficient double input-double output device.